Optimalisasi Pencucian Batubara Kalori Rendah Menggunakan Minyak Pelumas Dan Minyak Tanah Dengan Metode Flotasi - Marluga Banjarnahor, Ely; C Eka Putra, Jevie; Rahmi, Hisni (Jurnal Teknik dan Teknologi Tepat Guna, 2022)
PT Golden Great Borneo is classified as having low grade coal with an average calorific value of 4287 kcal/kg. Coal with low calories generally still contains impurities (mineral matter). The purpose of this study was to analyze the effect of the volume of lubricating oil and kerosene, solution pH, and Total Dissolved Solid (TDS) on coal recovery from coal washing using the flotation method. Coal washing uses the flotation method with a mixture of water, lubricating oil, and kerosene to further see the effect of pH, TDS on recovery. In testing lubricating oil and kerosene on recovery, coal from washing using the flotation method resulted in optimum recovery at a variation of 40:40 ml with a feed of 50 grams, the value of recovery was 92.4% and the correlation value between these two variables was sufficient, namely 0.35. While the results of the effect of pH and TDS on recovery by the flotation method, the optimum value in the variation of 40:40 ml with a pH value of 7 at the correlation value between these two variables is sufficient, namely 0.35 and TDS is known to be the optimum recovery result in a variation of 40: 40 ml with TDS value of 0.32 mg/l on the correlation value between these two variables is sufficient, namely 0.35.